Indian English in political discussions. Issue 1 (3rd June 2019) - Gargesh, Ravinder; Sharma, Anamika
Abstract: The present paper on 'verbal disputes' is a tribute to Professor Braj B. Kachru, who himself had a keen interest in the politics of language. This paper draws its data from three types of political discussions in India: a debate, an interview, and an altercation between the moderator and a guest on three different televised programme. This article analyses various aspects of political argumentation in the Indian context, including such macrolinguistic features as the setting of discussions, the socio‐cultural and political context, and the argumentation of participants, as well as the microlinguistic features of the texts generated in political discussions. Such features include patterns of code‐mixing and code‐switching, lexis, phonology, rhetoric, syntax, and the use of tag questions.